1992
DOI: 10.1159/000126316
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H<sub>1</sub> and H<sub>2</sub> Receptor Activation Stimulates ACTH and β-Endorphin Secretion by Increasing Corticotropin-Releasing Hormone in the Hypophyseal Portal Blood

Abstract: Histamine (HA) stimulates the release of adrenocorticotropic hormone (ACTH) and β-endorphin (β-END) via activation of central postsynaptic H1 or H2 receptors. The effect of HA is indirect and may involve the hypothalamic regulating factors corticotropin-releasing hormone (CRH), arginine vasopressin, or oxytocin (OT). We studied the effect of specific HA H1 or H2 receptor agonists on the concentration of CRH and OT in hypophyseal portal blood in urethane-anesthetized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…These results indicate that the effect of HA on ACTH secretion is not mediated via catecholaminergic neurons or modulated by a concomitant presence of activated adrenergic receptors. The results resemble our previous finding that the serotonergic system does not participate in the mediation of the HA-induced ACTH release [14]and strengthens the hypothesis that HA affects ACTH secretion primarily via a direct activation of arginine vasopressin and in particular corticotropin-releasing hormone neurons in the parvocellular parts of the paraventricular nucleus [8, 9, 11, 19]. Whereas HA-induced stimulation of the HPA axis seems to be independent of serotonergic or adrenergic receptor activation [14], present study], we have previously found that HA interact with prostaglandins [13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results indicate that the effect of HA on ACTH secretion is not mediated via catecholaminergic neurons or modulated by a concomitant presence of activated adrenergic receptors. The results resemble our previous finding that the serotonergic system does not participate in the mediation of the HA-induced ACTH release [14]and strengthens the hypothesis that HA affects ACTH secretion primarily via a direct activation of arginine vasopressin and in particular corticotropin-releasing hormone neurons in the parvocellular parts of the paraventricular nucleus [8, 9, 11, 19]. Whereas HA-induced stimulation of the HPA axis seems to be independent of serotonergic or adrenergic receptor activation [14], present study], we have previously found that HA interact with prostaglandins [13].…”
Section: Discussionsupporting
confidence: 89%
“…The ACTH antiserum (generously provided by the National Pituitary Agency, National Institute of Health) does not cross-react with β-endorphin or β-LPH and has less than 0.4% cross-reactivity with α- and β-melanocyte stimulating hormone. Synthetic human ACTH [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39](generously provided by the National Pituitary Agency, National Institute of Health) served as reference preparation and iodination. The least detectable quantity of ACTH was 1 pmol/l plasma, and the intra- and interassay coefficients of variation were 4 and 5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the following reasons it is possible that one of the routes by which stress increases ACTH and β-END release is caused by excitation of histaminergic neurons in the posterior hypothalamus, which in turn activates CRH neurons in the PVN: histaminergic nerve fibers project from the tuberomammillary nuclei to the PVN [25, 26]; HA increases CRH synthesis and release in the PVN [62, 63]; antiserum to CRH inhibit the HA-induced release of ACTH and β-END [64], and CRH as well as HA mediate the stress-induced release of ACTH and β-END [8, 9, 10, 11, 18]. CRH released to the portal circulation then stimulates the secretion of the POMC-derived peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of mast cells results in the release of histamine and other chemical messengers, 111 and histamine has been shown to increase levels of CRF in rats. 144, 145 This effect could be further enhanced by histamine receptor agonists or blocked by histamine receptor antagonists or anti-CRF. 144, 146, 147 In dog brain, mast cell degranulation results in an increase in histamine release and a subsequent increase in plasma cortisol and ACTH.…”
Section: Resultsmentioning
confidence: 99%